(2x+3y+1)dx+(4x+6y-5)=0

Simple and best practice solution for (2x+3y+1)dx+(4x+6y-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+3y+1)dx+(4x+6y-5)=0 equation:


Simplifying
(2x + 3y + 1) * dx + (4x + 6y + -5) = 0

Reorder the terms:
(1 + 2x + 3y) * dx + (4x + 6y + -5) = 0

Reorder the terms for easier multiplication:
dx(1 + 2x + 3y) + (4x + 6y + -5) = 0
(1 * dx + 2x * dx + 3y * dx) + (4x + 6y + -5) = 0

Reorder the terms:
(1dx + 3dxy + 2dx2) + (4x + 6y + -5) = 0
(1dx + 3dxy + 2dx2) + (4x + 6y + -5) = 0

Reorder the terms:
1dx + 3dxy + 2dx2 + (-5 + 4x + 6y) = 0

Remove parenthesis around (-5 + 4x + 6y)
1dx + 3dxy + 2dx2 + -5 + 4x + 6y = 0

Reorder the terms:
-5 + 1dx + 3dxy + 2dx2 + 4x + 6y = 0

Solving
-5 + 1dx + 3dxy + 2dx2 + 4x + 6y = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 1dx + 3dxy + 2dx2 + 4x + 5 + 6y = 0 + 5

Reorder the terms:
-5 + 5 + 1dx + 3dxy + 2dx2 + 4x + 6y = 0 + 5

Combine like terms: -5 + 5 = 0
0 + 1dx + 3dxy + 2dx2 + 4x + 6y = 0 + 5
1dx + 3dxy + 2dx2 + 4x + 6y = 0 + 5

Combine like terms: 0 + 5 = 5
1dx + 3dxy + 2dx2 + 4x + 6y = 5

Add '-4x' to each side of the equation.
1dx + 3dxy + 2dx2 + 4x + -4x + 6y = 5 + -4x

Combine like terms: 4x + -4x = 0
1dx + 3dxy + 2dx2 + 0 + 6y = 5 + -4x
1dx + 3dxy + 2dx2 + 6y = 5 + -4x

Add '-6y' to each side of the equation.
1dx + 3dxy + 2dx2 + 6y + -6y = 5 + -4x + -6y

Combine like terms: 6y + -6y = 0
1dx + 3dxy + 2dx2 + 0 = 5 + -4x + -6y
1dx + 3dxy + 2dx2 = 5 + -4x + -6y

Reorder the terms:
-5 + 1dx + 3dxy + 2dx2 + 4x + 6y = 5 + -4x + -6y + -5 + 4x + 6y

Reorder the terms:
-5 + 1dx + 3dxy + 2dx2 + 4x + 6y = 5 + -5 + -4x + 4x + -6y + 6y

Combine like terms: 5 + -5 = 0
-5 + 1dx + 3dxy + 2dx2 + 4x + 6y = 0 + -4x + 4x + -6y + 6y
-5 + 1dx + 3dxy + 2dx2 + 4x + 6y = -4x + 4x + -6y + 6y

Combine like terms: -4x + 4x = 0
-5 + 1dx + 3dxy + 2dx2 + 4x + 6y = 0 + -6y + 6y
-5 + 1dx + 3dxy + 2dx2 + 4x + 6y = -6y + 6y

Combine like terms: -6y + 6y = 0
-5 + 1dx + 3dxy + 2dx2 + 4x + 6y = 0

The solution to this equation could not be determined.

See similar equations:

| 4c-6-3x=2+5x | | x/5=0.41 | | 11X=9X+46 | | Y+6=-5(x+9) | | Y+2=-6(x-7) | | 3z^2+10z+3=0 | | 6x^2+x-75=0 | | -40=-(4v-4)-2(6-6v) | | Y+1=-7(x+2) | | 2+2y+-3=11 | | (2x+3y+1)dx=-(4x+6y-5)dy | | 11v+14x=3450 | | x+2.1x=-26.4 | | y-45+6x=0 | | 16=s/2 | | -2(2x+3)=18 | | -16=4(-v-6)-3(4-8v) | | 6x-3=k(-2x+1) | | 24=-4(1-7n)+7(n+4) | | -4(5x-7)=168 | | 8k+54=-14 | | -328=-8(-7x-7)+8 | | 10x^2+120x-36=0 | | 16x=2x+84 | | (4-8x)2+(x)2=400 | | 81=-5(1-8a)+3a | | 12x+6=100 | | -7(5k-6)=-168 | | 8m-14=59 | | 130=4c+225 | | -5(-7v+8)=-215 | | sin(x)(sin(x)+1)=0 |

Equations solver categories